Toward a Richer Picture of the Mobility Needs of Older Americans. Issue 4 (2nd October 2019) - Loukaitou-Sideris, Anastasia; Wachs, Martin; Pinski, Miriam
Abstract: Problem, research strategy, and findings: People older than 65 are the most rapidly growing segment of the U.S. population, yet our cities and transportation systems are not age friendly. Low-income, minority, older adults residing in inner-city neighborhoods are largely transit dependent, rely significantly on walking for transportation, and thus have particular mobility needs. We used a mixed-methods approach that drew information from the California Household Travel Survey but also from direct interaction (through focus groups, interviews, and neighborhood walking audits) with 81 low-income, inner city–living older adults to understand their travel patterns and mobility challenges and needs. We find that despite some positive mobility indicators in the inner city (mixed-use environment, frequent bus service, and short travel distances), these elders face significant mobility challenges because of a deteriorated built environment, heavy traffic, homelessness, and crime. A limitation of this research is that the small sample did not allow the study of possible gender or race/ethnicity differentiation in the travel patterns and needs of older adults. Takeaway for practice: Planners should not rely only on information from the census and other aggregate data sources to understand the mobility needs of older adults but should complement this information with direct interaction with the communities for which they are planning. Although some social problems limiting the mobility of older adults are difficult to tackle, environmental and streetscape improvements can significantly enhance their mobility.